Novel homozygous missense mutation in GAN associated with Charcot-Marie-Tooth disease type 2 in a large consanguineous family from Israel. Issue 1 (December 2016) - Aharoni, Sharon; Barwick, Katy; Straussberg, Rachel; Harlalka, Gaurav; Nevo, Yoram; Chioza, Barry; McEntagart, Meriel; Mimouni-Bloch, Aviva; Weedon, Michael; Crosby, Andrew
Abstract Background CMT-2 is a clinically and genetically heterogeneous group of peripheral axonal neuropathies characterized by slowly progressive weakness and atrophy of distal limb muscles resulting from length-dependent motor and sensory neurodegeneration. Classical giant axonal neuropathy (GAN) is an autosomal recessively inherited progressive neurodegenerative disorder of the peripheral and central nervous systems, typically diagnosed in early childhood and resulting in death by the end of the third decade. Distinctive phenotypic features are the presence of "kinky" hair and long eyelashes. The genetic basis of the disease has been well established, with over 40 associated mutations identified in the geneGAN, encoding the BTB-KELCH protein gigaxonin, involved in intermediate filament regulation. Methods An Illumina Human CytoSNP-12 array followed by whole exome sequence analysis was used to identify the disease associated gene mutation in a large consanguineous family diagnosed with Charcot-Marie-Tooth disease type 2 (CMT-2) from which all but one affected member had straight hair. Results Here we report the identification of a novelGAN missense mutation underlying the CMT-2 phenotype observed in this family. Although milder forms of GAN, with and without the presence of kinky hair have been reported previously, a phenotype distinct from that was investigated in this study. All family members lacked common features of GAN, including ataxia, nystagmus, intellectual disability, seizures, and central nervous system involvement. Conclusions Our findings broaden the spectrum of phenotypes associated withGAN mutations and emphasize a need to proceed with caution when providing families with diagnostic or prognostic information based on either clinical or genetic findings alone.